The role of veterinary research laboratories in the provision of veterinary services - Verwoerd, D W (Revue scientifique et technique (International Office of Epizootics), 1998)
Veterinary research laboratories play an essential role in the provision of veterinary services in most countries. These laboratories are the source of new knowledge, innovative ideas and improved technology for the surveillance, prevention and control of animal diseases. In addition, many laboratories provide diagnostic and other services. To ensure the optimal integration of various veterinary activities, administrators must understand the functions and constraints of research laboratories. Therefore, a brief discussion is presented of the following: organisational structures methods for developing research programmes outputs of research scientists and how these are measured the management of quality assurance funding of research. Optimal collaboration can only be attained by understanding the environment in which a research scientist functions and the motivational issues at stake.